Business Plan for a Second-Hand Clothing Store in Vietnam - Nguyen, Dai Long (2025)
This bachelor thesis aims to develop a business plan for a business established under the name “ShipShape 2Hand” in the coastal tourist city of Vung Tau, Vietnam. ShipShape 2Hand sells second-hand clothing products such as shirts, pants, and skirts. The Vietnamese consumer trend for fashion has increased in recent years, creating conditions for brands like ShipShape 2Hand to enter the market, develop, and expand, benefiting from the thrifty and calculating spending trend of potential customers in Vietnam, making the niche market such as used clothes have more future development. The methods, marketing strategies, distribution channels, and operational processes will be studied and implemented for the ShipShape 2Hand business model. The thesis will show whether this business model can be implemented or not.